STUDI EMPIRIS PENGARUH PERTUMBUHAN PERUSAHAAN, STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hayuningtyas Pramesti Dewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study examines the effect of company growth, capital structure and profitability on the value of property and real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Data were analyzed using multiple regression test and hypotheses were tested using t test and f test. The test results state that Capital Structure and Profitability partially affect firm value while firm growth has no effect on firm value. The three simultaneously affect the value of the company.